Risk‐Free Rates and Variance Futures Prices. Issue 10 (23rd December 2015) - Rompolis, Leonidas S.
Abstract: This paper investigates the relation between risk‐free rates and ex‐ante market volatility. It derives a theoretical model implying a negative linear relation between risk‐free rates and variance futures prices. The latter are employed as a direct market‐based ex‐ante estimate of risk‐neutral volatility. Empirical analysis, conducted using LIBOR and variance futures prices written on the S&P 500 index, indicates that the predictions of the model are supported by the data. The paper also provides evidence that, first, this negative relation varies smoothly over time following business cycles, and, second, the variance risk premium is a significant component of this documented relation. © 2015 Wiley Periodicals, Inc. Jrl Fut Mark 36:943–967, 2016